Tidal-current Power Generation by Vertical Axis Underwater Turbine with Diffuser in Coastal Area of Peninsular Malaysia - Azman, Idris; Azim, Arshad; Shahrani, Anuar; Achmmmad, Shukrie (2014)
Tidal water current in Malaysia can be used as a resource to generate electricity by using turbine. However, the velocity of water is very low and the installation of diffuser can help in accelerating the water velocity. The aim of this research is to study the effect on velocity when a diffuser is in installed in a turbine and the potential power generation produced by the turbine.